Regulation of purine de novo synthesis in cultured human fibroblasts: the role of P-ribose-PP - Gordon, R B; Thompson, L; Johnson, L A; Emmerson, B T (Biochimica et biophysica acta, 1979)
Procedures for assaying the rate of purine de novo synthesis in cultured fibroblast cells have been compared. These were (i) the incorporation of [(14)C]-glycine or [(14)C]formate in alpha-N-formylglycinamide ribonucleotide (an intermediate in the purine synthetic pathway) and (ii) the incorporation of [(14)C]-formate into newly synthesised cellular purines and purines excreted by the cell into the medium. Fibroblast cells, derived from patients with a deficiency of hypoxanthine phosphoribosyltransferase (HPRT-) (EC 2.4.2.8) and increased rates of purine de novo synthesis, were compared with fibroblasts from healthy subjects (HPRT+). Fetal calf serum, which was used to supplement the assay and cell growth medium, was found to contain sufficient quantities of the purine base hypoxanthine to inhibit purine de novo synthesis in HPRT+ cells. This inhibition was the basis of differentiation between HPRT- and HPRT+ cells. In the absence of added purine base, both cell types had similar capacities for purine de novo synthesis. This result contrasts with the increased rates of purine de novo synthesis reported for a number of human HPRT- cells in culture but conforms recent studies made on human HPRT- lymphoblast cells. The intracellular concentration and utilisation of 5-phosphoribosyl-1-pyrophosphate (P-Rib-PP), a substrate and potential controlling factor for purine de novo synthesis, were determined in HPRT- and HPRT+ cells. The rate of utilisation of P-Rib-PP in the salvage of free purine bases was far greater than that in purine de novo synthesis. Although HPRT- cells had a 3-fold increase in P-Rib-PP content, the rate of P-Rib-PP generation was similar to HPRT+ cells. Thus, in fibroblasts, the concentration of P-Rib-PP appears to be critical in the control of de novo purine synthesis and its preferential utilisation in the HPRT reaction limits its availability for purine de novo synthesis. In vivo, HPRT+ cells, in contrast to HPRT- cells, may be operating purine de novo synthesis at a reduced rate because of their ability to reutilise hypoxanthine.